IV FECI-TOO - Feira de Ciências de Toledo como espaço de discussão a partir dos Indicadores de Alfabetização Científica e Tecnológica - Albuquerque, Gean Carlos de Souza (2024)
Scientific and Technological Literacy (STL) provides individuals with a worldview focused on understanding the relationships and influences of science and technology in society. Its development routinely occurs in schools but extends beyond these spaces. Science Fairs, for instance, are events for the production and dissemination of science and technology, occurring in both formal and non-formal educational settings, providing unique moments for promoting STL. Through this study, we relate research findings, highlighting references on STL, Structuring Axes of Scientific Literacy (SL), and the Dimensions of SL for formal educational settings, and for non formal settings, the Indicators of SL. Our aim is to explore the existing relationship between STL and Science Fairs through the Indicators of SL. These indicators, in addition to being part of the theoretical framework, also serve as our analytical tool. This tool was adapted to the reality of Science Fairs, specifically the IV Science Fair of Toledo (IV FECI-TOO). Data collection for this research at this Fair was conducted through written documents submitted by exhibitors for registration and recordings of project presentations on the day of the event. Analysis of these documents was aided by the ATLAS.ti software. As a result of these analyses, we identified the presence of STL at the Science Fair through the Scientific, Social Interface, Institutional, and Interaction Indicators. The most recurring indicator found was the Scientific Indicator, which was more deeply developed. The second most recurring was the Social Interface Indicator, demonstrating social issues involving personal and global contexts. The Institutional Indicator was superficially developed as a means of presenting the educational institution or science club to which the exhibitors belonged. The Interaction Indicator was identified through spontaneous interactions developed in the form of physical, aesthetic-affective, and primarily cognitive interaction through questioning and dialogue. This research highlights in project presentations the better development of scientific and social issues and indicates the absence of institutional and interactive aspects that could contribute to the development of STL. The research facilitated understanding Science Fairs as a process rather than just an isolated event, as well as proposing new ways regarding the construction of scientific knowledge in this process. The research contributed to an understanding of the complexity of the relationship between Science Fairs and STL, indicating the potential to be achieved if supported by the premises of this relationship.